Inequality, Well-being and Institutions in Latin America and the Caribbean - Jaideep Oberoi; Syed Ahsan (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper focuses on the role of institutions in the fight against poverty and inequality. Our view of institutions encompasses formal rules designed by polity (including those in the legal and economics sphere such as rules of property rights, contracts and liabilities) as well as informal rules (usually labelled social capital) that have emerged over the history of one's civilisation. The inclusion of health, nutrition, and literacy indicators in defining well-being (or, non-income poverty à la capability approach of Amartya Sen) allows a rich discussion of policy interventions. While both orientations as to the concepts of poverty, inequality and institutions are expounded on a priori reasoning, empirical analysis with LAC data prove rewarding. Quality of institutions (measured by a composite variable called institutional capital, IC) turns out to be a key factor explaining well-being. Further where the level of income is also important to the explanation, the quantitative role of the institutional factor dominates that of the income variable. Within IC, political stability (or lack of violence) appeared to provide the more precise estimates in every case. Consequently we argue that the foremost policy interventions ought to be in the areas of building both adequate formal institutions, as well as creating an enabling environment for the informal institutions (such as social capital) to flourish and find their own roots. The principal focus of the policy debate must centre on the mutual interaction of market as well as non-market institutions in reducing poverty broadly speaking
Keywords: 330